2018
DOI: 10.1088/1361-6463/aa98af
|View full text |Cite
|
Sign up to set email alerts
|

Pedestal formation of all-semiconductor gratings through GaSb oxidation for mid-IR plasmonics

Abstract: Mid-IR localized surface plasmon resonances (LSPR) have been demonstrated in nano-ribbons of highly Si-doped InAsSb alloys on GaSb substrates. We show that the slow, steady and selective oxidation of GaSb in water leads to an all-semiconductor mid-IR pedestal configuration consisting of highly doped InAsSb plasmonic resonators on top of GaSb pedestals embedded in an amorphous oxide layer. The homogeneity of the pedestal structure is imaged with an attenuated-total reflection Fourier transform infrared (ATR-FTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Details on the fabrication can be found in previous work [3,28]. 12,12,13,13,14,14,15,15,16,16,17,17,18,18,19,19,19-Heptadecafluorononadecylphosphonic acid (Cas N. 625095-76-3) and (6-{2-[2-(2-Methoxy-ethoxy)-ethoxy]-ethoxy}-hexyl)phosphonic acid (Cas N. 1049677-18-0) were synthesized by Sikemia. For the sake of simplicity, in the following, we will call the phosphonic acid with the fluorinated terminate group FDPA and the phosphonic acid with the methoxy-terminated ethylene glycol group EGPA.…”
Section: Mid-ir Reflective Layer Structures and Plasmonic Grating Fabmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on the fabrication can be found in previous work [3,28]. 12,12,13,13,14,14,15,15,16,16,17,17,18,18,19,19,19-Heptadecafluorononadecylphosphonic acid (Cas N. 625095-76-3) and (6-{2-[2-(2-Methoxy-ethoxy)-ethoxy]-ethoxy}-hexyl)phosphonic acid (Cas N. 1049677-18-0) were synthesized by Sikemia. For the sake of simplicity, in the following, we will call the phosphonic acid with the fluorinated terminate group FDPA and the phosphonic acid with the methoxy-terminated ethylene glycol group EGPA.…”
Section: Mid-ir Reflective Layer Structures and Plasmonic Grating Fabmentioning
confidence: 99%
“…In a long-time air oxidation study, it could be shown that a 3 nm thick native oxide layer appears on GaSb within one day whereas after 3 years this layer increases only moderately by 1 nm [9]. The hydrolytic stability for InAs in neutral water was reported [10], but GaSb oxidizes in an aqueous environment [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…To validate the grafting of trimethoxysilanes on III−V semiconductor surfaces, we additionally performed X-ray photoelectron spectrometry (XPS). An XPS survey scan acquired on InAs surfaces before and after the grafting of 12,12,13,13,14,14,15,15,16,16,17,17 3b. The molecule's high content of Fluor serves as a marker in XPS.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The hydrolytic stability of InAs in neutral water was reported . However, GaSb is not stable in aqueous environment. ,, A water-free surface chemistry is thus required to prevent the oxidation of GaSb in water, which is much faster and more detrimental than the air oxidation. Trimethoxysilane derivatives are an interesting approach for monolayer formation on metal oxides, and we demonstrate in the following the successful surface modification by silane surface chemistry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation